On orthogonality preserving cubic stochastic operator defined on 1-dimensional simplex - Mukhamedov, Farrukh; Pah, Chin Hee; Rosli, Azizi (2019)
In this paper, we consider the cubic stochastic operator (CSO) defined on 1-dimensional simplex, S 1 . We provide a full description of orthogonal preserving (OP) cubic stochastic operators on the simplex. We provide full description of the fixed points subject to two different parameters for the Volterra OP CSO on the simplex. In the last section we describe the behaviour of the fixed points.